Patient practitioner assistive communications ontology - Forbes, David; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2018)
In the previous chapter, ontology engineering including different methodologies, design criteria, verification process, and editor tool are presented. That gives a general understanding of ontology development. In this chapter, we present specifically the development of PPAC ontology.